Interfacial Electronic Modulation of Dual-Monodispersed Pt–Ni3S2 as Efficacious Bi-Functional Electrocatalysts for Concurrent H2 Evolution and Methanol Selective Oxidation - Zhao, Qianqian; Zhao, Bin; Long, Xin; Feng, Renfei; Shakouri, Mohsen; Paterson, Alisa; Xiao, Qunfeng; Zhang, Yu; Fu, Xian‑Zhu; Luo, Jing‑Li (Nano-Micro Letters, 2024)
Constructing the efficacious and applicable bi-functional electrocatalysts and establishing out the mechanisms of organic electro-oxidation by replacing anodic oxygen evolution reaction (OER) are critical to the development of electrochemically-driven technologies for efficient hydrogen production and avoid CO2 emission. Herein, the hetero-nanocrystals between monodispersed Pt (~ 2 nm) and Ni3S2 (~ 9.6 nm) are constructed as active electrocatalysts through interfacial electronic modulation, which exhibit superior bi-functional activities for methanol selective oxidation and H2 generation. The experimental and theoretical studies reveal that the asymmetrical charge distribution at Pt–Ni3S2 could be modulated by the electronic interaction at the interface of dual-monodispersed heterojunctions, which thus promote the adsorption/desorption of the chemical intermediates at the interface. As a result, the selective conversion from CH3OH to formate is accomplished at very low potentials (1.45 V) to attain 100 mA cm−2 with high electronic utilization rate (~ 98%) and without CO2 emission. Meanwhile, the Pt–Ni3S2 can simultaneously exhibit a broad potential window with outstanding stability and large current densities for hydrogen evolution reaction (HER) at the cathode. Further, the excellent bi-functional performance is also indicated in the coupled methanol oxidation reaction (MOR)//HER reactor by only requiring a cell voltage of 1.60 V to achieve a current density of 50 mA cm−2 with good reusability. Highlights: 1 The well-conceived Pt–Ni3S2 heteronanocrystals with dual-monodispersed characteristics are synthesized through interfacial electronic modulation. 2 The asymmetrical charge distribution at Pt–Ni3S2 hetero-interface results in the formation of high-valent Ni sites and negatively-charged Ptδ−. 3 It eventually accelerates water dissociation and achieves the steady concurrent generation of value-added formate and hydrogen.